Signifance of Liver Ductal Plate Malformation in Differential Diagnosis of Autosomal Recessive Polycystic Kidney Disease: An Autopsy Case - Kivilcim Eren Erdogan; Sevil Karabag; seyda Erdogan; Figen Doran (Çukurova Üniversitesi Tıp Fakültesi Dergisi, 2015)
Cystic renal diseases are a group of disorders that cause neonatal deaths. Autosomal recessive polycystic kidney disease (ARPKD) is a rare entity which may be associated with liver disorders. Presenting autopsy case was stillbirth in 31 + 1 gestational week. In postmortem autopsy,viewed through the capsule, the renal surface was filled by innumerable miniature cysts about 1 mm in diameter. istopathological examination revealed multiple cysts of variable size in the renal medulla and tortuosity, elongation of ductal plate of liver. The autopsy was evaluated as ARPKD and ductal plate malformation. This disorder is not usually compatible with life. Some of the other cystic kidney diseases have better clinical outcome and must be distinguished from ARPKD. [Cukurova Med J 2015; 40(Suppl 1): 18-21]